When a Dream Becomes a Nightmare: Why do Indigenous australian Medical Students Withdraw from Their Courses?. Issue 1 (22nd July 2008) - Ellender, Isabel; Drysdale, Marlene; Chesters, Janice; Faulkner, Susan; Kelly, Heather; Turnbull, Leanne
Abstract: This paper investigates reasons Indigenous Australian medical students gave for leaving their courses prior to graduation. Indigenous students who had withdrawn or deferred from their medical courses were asked about the barriers and disincentives that had dissuaded them from graduating. Although the response rate to the questionnaire was very low, it opened up a way of looking at the particular experiences of Indigenous students. Of the 12 responses, the most prominent reason given for withdrawing was financial. Most were satisfied with enrolment processes but a number were disappointed with their courses and with teaching methods. More support from the university was the only encouragement that would have persuaded most respondents to continue. This paper explores the reasons for the high rate of withdrawal of Indigenous medical students and concludes by suggesting ways in which secondary schools, universities and their medical schools could respond to the recruitment and retention of Indigenous medical students.